Kappa free light chain index in CSF diagnostics: the impact of different immunoglobulin isotypes - Schmidauer, Martin; Berek, Klaus; Auer, Michael; Di Pauli, Franziska; Föttinger, Fabian; Krajnc, Nik; Deisenhammer, Florian; Bsteh, Gabriel; Walde, Janette; Hegen, Harald (Frontiers in Immunology, 2026)
BackgroundThe kappa free light chain (κ-FLC) index is a sensitive marker of intrathecal immunoglobulin (Ig) synthesis and is increasingly used in cerebrospinal fluid (CSF) analysis of patients with suspected multiple sclerosis (MS). The relative contribution of the different Ig isotypes to intrathecal κ-FLC production remains unclear.MethodsWe retrospectively analysed CSF data from patients with a first demyelinating event suggestive of MS enrolled in studies at the Medical Universities of Innsbruck and Vienna. Of all included patients, results on Ig and κ-FLC concentrations in CSF and serum were available. Linear regression analysis was used to assess the impact of Ig intrathecal fractions (IF) on κ-FLC index.ResultsA total of 188 patients with a median age of 31 (25-39) years and a predominantly female sex distribution (62%) were included. The κ-FLC index was significantly higher in patients with isolated intrathecal IgG synthesis [32.5 (17.7-81.0); n=130] compared to patients without intrathecal immunoglobulin production [3.0 (2.0-5.9); p<0.001; n=18] and was further elevated in patients with both intrathecal IgG and IgM synthesis [68.4 (48.4-120.6); n=29]. Both IgG and IgM IF independently contributed to the κ-FLC index in linear regression analysis, with IgG IF having approximately 3.5 times the effect size of IgM IF. Exploratory analysis of the contribution of IgA IF to κ-FLC index revealed qualitatively the same results.ConclusionIncrease of κ-FLC index in patients with MS is predominantly due to an intrathecal IgG synthesis, while the contribution of intrathecal IgM is less frequent and quantitatively low.